Effect of microwave radiation on optical characteristics of thin gold films - Boltovets, P.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The possibility to use a complex of chemical and physical factors to form sensor surface with tunable properties was considered. It was demonstrated that the simultaneous treatment of thin gold films with guanidine thiocyanate and microwave radiation results in changes in the width of the surface plasmon resonance curve, its amplitude and position of its minimum. Thereby, the combination of these two factors can allow obtaining surface structures with controllable parameters.